The Influence of Liquidity, Capital Adequacy, and Profitability on Financial Stability in Islamic Commercial Banks in Indonesia for the 2013-2023 Period - Sari, Astafirla Dewinda; Setiawan, Setiawan (Journal of Applied Islamic Economics and Finance, 2025)
This study is expected to determine and analyze the effect of liquidity, capital adequacy, and profitability on financial stability. The independent variables used are Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), and Net Income (NI). While the dependent variable used is Z-score. The data used in this study are secondary data derived from the annual financial statements of Islamic Commercial Banks. By using purposive sampling, namely 16 Islamic Commercial Banks in Indonesia which were selected according to predetermined criteria. The data analysis method uses panel data unbalance regression analysis. The test results show that partially FDR and CAR have a positive effect on financial stability, while partially NI has no effect on financial stability. While simultaneously the three independent variables affect financial stability.